The Role of Export Entrepreneurship Effective Factors in Export Performance - Asghari, E.; Rostami, A. R. R. (Engineering, Technology & Applied Science Research, 2017)
This research aims to investigate the role of export entrepreneurship effective factors in export performance. Research statistical population contains sales managers and top managers working in manufacturing companies of precious and decorative stones in Firuzeh, a city in Iran. In order to gather data, a questionnaire consisting of 32 questions has been used. The validity of the questionnaire was confirmed by supervisors and advisors and its reliability has been assessed (0.865) using Cronbach’s alpha coefficient. Five hypotheses have been proposed for this research. Two methods of descriptive and inferential statistics have been used to analyze the data in this study. In the descriptive part, frequency number, frequency percentage, and frequency graph have been employed. Statistical analysis on data collected show that the variables of management commitment, resources, and the intensity of competition have significant positive impact on export entrepreneurship while the variable market distance does not have significant positive impact on export entrepreneurship. In addition, export entrepreneurship has a significant positive impact on export performance.